A Hidden Treasure: The Borneo Mistletoes - Lim, Ya Chee; Rajabalaya, Rajan; David, Sheba Rani (Pharmacognosy Reviews)
The European mistletoe, Viscum album, is the most common consumed adjuvant among cancer patients in Europe. Its success warrants a report on three most apparent mistletoes found in Borneo Island, namely Scurrula ferruginea, Macrosolen cochinchinensis, and Dendrophthoe curvata. The traditional and pharmacological uses of these mistletoes include antibacterial, anticancer, antiviral, antihypertensive, antioxidative, and cytotoxic effects. Phytochemicals such as flavonols, alkaloids, tannins, and gallic acid have been reported in one of these mistletoes. This review discusses the potential of these mistletoes as therapeutic agents.
Keywords: Cancer; Dendrophthoe curvata; Macrosolen cochichinensis; plant; Scurrula ferruginea; traditional medicine; tropical